Book Review: 'Mountains to the Sea: Solving New Zealand’s Freshwater Crisis' - Baisden, Troy (New Zealand Science Review, 2019)
Mike Joy has become a scientist known widely by Kiwis because he regularly sticks his head above the parapet to argue for our freshwater environments and the critters that live in them. The new book he has edited aims to sidestep arguments and focus on finding ways of thinking that lead to solutions. The title Mountains to the Sea: Solving New Zealand’s Freshwater Crisis should cause any reviewer to ask whether the authors truly deliver solutions. Perhaps unsurprisingly, the answer is both: yes, and no.